Cerebral Microdialysis: Going Deep into Brain Biochemistry for a Better Understanding of Pathomechanisms of Acute Brain Injury - Gupta, Deepak Kumar; Mazzeo, Anna Teresa (Indian Journal of Neurosurgery, 2017)
Patients with traumatic brain injury (TBI) have variable outcomes subject to intracranial hypertension, ischemia, hypotension, and various biochemical alterations. Multimodality neurointensive monitoring is standard of care for decision making in all severe TBI cases at present in most neurotrauma units. Neuromonitoring tools, such as cerebral microdialysis, may contribute to understanding the pathomechanisms of acute brain injury, provide an early warning of secondary cerebral deterioration (therapeutic window of opportunity), and help in selecting the patients most suitable to benefit from this very invasive surgical rescue therapy. Cerebral microdialysis can be used as a measure of the effect of decompressive craniectomy on neurochemistry derangement and brain energy crisis jeopardizing the injured brain. Present review discusses the cerebral microdialysis, its usefulness, and role in prognostication of severe TBIs, especially in patients post-decompressive craniectomy. The authors also discuss the current consensus guidelines on usage of cerebral microdialysis in TBI patients.
Keywords: cerebral microdialysis; severe traumatic brain injury; decompressive craniectomy; ischemia; mitochondrial dysfunction